ANALISIS KANDUNGAN ZAT PEMANIS (Siklamat dan Sakarin) PADA SELAI BUAH TIDAK BERMEREK YANG DIJUAL DI BEBERAPA PASAR TRADISIONAL KOTA MEDAN TAHUN 2016 - nyanyu mashitoh; Evawany Y Aritonang; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Jam fruit is a refined products with the basic fruits with variously types that well known and many people like it. In the manufacturing procces, manufacturers often use artificial sweeteners to replace natural sweeteners. Artificial sweeteners are the most widely used is the cyclamate and saccharin because the price is much cheaper than the natural sweetener, it is very easy to find, so as to reduce production costs and provide more money for producers. In some studies it was found that the use of artificial sweeteners that do not qualify will cause carcinogenic diseases. This research is the descriptive survey to know the types of a sweetener as food additivies in jam fruit not branded in the traditional market town of Medan. The sample was taken by purposive sampling from Helvetia market, Pringgan market, Kampung Lalang market, Simpang Limun market and Aksara market. Analysis qualitative of cyclamate a sweetener to do with the deposition method and analysis of saccharine with extraction reagent colour test in Regional Health Laboratory, Medan . The results showed that in 15 samples of jams fruit that are five traditional market town of Medan containing no artificial sweeteners saccharin and one samples (6,7%) of jam fruit containing artificial sweetener cyclamate, samples from Kampung Lalang traditional markets. It is suggested to consumers so remain selective foods especially product jam fruits. Keywords  :  Fruits Jams, Cyclamate, Saccaharine, Artifical Sweeteners